Does Corporate Social Responsibility Disclosure Have Relevance To Profit And Book Value? - Indhung Listyaningrum; Katika Hendra Titisari; Siti Nurlaela (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2020)
This research was aimed to examined and analyzed the value relevance of accounting information by disclosured of Corporate Social Responsibility (CSR) as a moderating variabel in banking sector companies. The population of this research was by 11 banking companies registered on the BEI (Bursa Efek Indonesia) in the period of 2015 -2018. From the population, reasearcher found 44 samples by used purposive sampling method. The hypothesis test of this research used multiple linear regression by Moderated Regression Analysis (MRA) approach. The independent variables of this research were earning and book value. CSR as an independen variable and moderating variable. While the dependent variable was the stock price. The result of this research was to indicated that the earning and book value were relevance to the value of accounting information. While CSR disclosure as an independent variable and moderating variable didn’t have relevance to the value of accounting information. The moderating result of CSR disclosure weren’t able to substantiated the earning and book value.